In vitro selection of an RNA aptamer yields an interleukin-6/interleukin-6 receptor interaction inhibitor. Issue 5 (2nd January 2021) - Ando, Takehiro; Yamamoto, Mizuki; Takamori, Yukio; Tsukamoto, Keita; Fuji, Daisuke; Kawakami, Takashi
ABSTRACT: Interleukin-6 (IL-6) binds to the IL-6 receptor (IL-6R) subunit, related to autoimmune diseases and cytokine storm in COVID-19. In this study, we performed systematic evolution of ligands by exponential enrichment and identified a novel RNA aptamer. This RNA aptamer not only bound to IL-6R with a dissociation constant of 200 n m, but also inhibited the interaction of IL-6R with IL-6.